Ecotourism is becoming a major focus of development - Poon, Auliana (Caribbean Futures Port-of-SpainTT, 1991)
This segment of the report presents the view that ecotourism offers tremendous opportunities for the development of tourism. The competitive advantage of Eastern and Southern Caribbean countries is shown in the accessibility of their eco-attractions.